Age influence on hypersensitivity pneumonitis induced in mice by exposure to Pantoea agglomerans. (16th September 2013) - Lemieszek, Marta Kinga; Chilosi, Marco; Golec, Marcin; Skórska, Czesława; Dinnyes, Andras; Mashayekhi, Kaveh; Vierlinger, Klemens; Huaux, Francois; Wielscher, Matthias; Hofner, Manuela; Yakoub, Yousof; Pastena, Chiara; et al.
Abstract: Hypersensitivity pneumonitis (HP) represents the immunologically mediated lung disease induced by repeated inhalations of a wide variety of certain finely dispersed organic antigens. In susceptible subjects, these inhalations provoke a hypersensitivity reaction characterized by intense inflammation of the terminal bronchioles, the interstitium and the alveolar tree. The inflammation often organizes into granulomas and may progress to pulmonary fibrosis. Our previous work indicated that cell extract of gram-negative bacteria Pantoea agglomerans (SE-PA) causes, in young C57BL/6J mice, pulmonary changes that are very similar to the clinical manifestations of HP in men. The purpose of presented studies was to describe the response of mice immune system while exposed to SE-PA. Particular attention was paid to examine the age influence on SE-PA induced inflammation and fibrosis in lung tissue. We used 3- and 18-month-old C57BL/6J mice. Lung samples were collected from untreated mice and animals exposed to harmful agent for 7 and 28 days. HP development was monitored by histological and biochemical evaluation. Using ELISA tests, we examined concentration of pro- and anti-inflammatory cytokines in lung homogenates. Our study demonstrated again that SE-PA provokes in mice changes typical for the clinical picture of HP, and that successive stages of disease (acute, subacute and chronic) might be obtained by modulation of time exposure. Furthermore, we found that animals' age at the time of sensitization influences the nature of observed changes (cytokine expression pattern) and the final outcome (reaction intensity and scale of fibrosis).